2(5x-1)=6

Simple and best practice solution for 2(5x-1)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5x-1)=6 equation:


Simplifying
2(5x + -1) = 6

Reorder the terms:
2(-1 + 5x) = 6
(-1 * 2 + 5x * 2) = 6
(-2 + 10x) = 6

Solving
-2 + 10x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 10x = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 10x = 6 + 2
10x = 6 + 2

Combine like terms: 6 + 2 = 8
10x = 8

Divide each side by '10'.
x = 0.8

Simplifying
x = 0.8

See similar equations:

| y=100x+3+506x-x | | (2/3)×7 | | 4(x+6)=-5(x+1)+3(4-x)+12x+17 | | d/4=0.3 | | (4y-2)/5=(y-6)/4 | | 5(4x+3)+3x+3=41 | | 9x-8y=-67 | | 19.5-x=7.2 | | 12x^2+24+5=4x+5 | | y=x+x+20 | | 7x+14y=49 | | 8(-7)=6(-7)-14 | | 2.5(1-x)=1 | | 4(3-u)=u+22+2u | | -8=-4n+8 | | 10+13y=1 | | 5(1-3a)=-85 | | y=177.46x-7e+06 | | 225y-80x=0 | | 108=3(-8+4x) | | 3x^2-12=-39 | | (X+4)(6)(x)=840 | | 4x^2-12x-12y+21=0 | | 6(6+3r)=108 | | 1/5x-18=2 | | 19.5-7.2=x | | 1/7x-3=6 | | 21+3c-7(2-3c)=4(c-5)+3c+27 | | 15(4n-4)=-60 | | 2(x-6)+2=9x-(7x+6)-4 | | 7/2x=3/x-5 | | 15=t/4-1 |

Equations solver categories